Coumarins from Murraya paniculata (Rutaceae) - Syed Abdul Aziz, Saripah Salbiah; Md.Sukari, Mohd. Aspollah; Rahmani, Mawardi; Kitajima, Mariko; Aimi, Norio; Ahpandi, N. J. (Malaysian Society of Analytical Sciences, 2010)
Phytochemical study on leaves of Murraya paniculata have yielded four coumarins of auraptene(1), transgleinadien (2), 5,7-dimethoxy-8-(3-methyl-2-oxo-butyl)coumarin (3) and toddalenone(4). The compounds were isolated using chromatographic methods and identified using spectroscopic techniques. Antimicrobial activity evaluation on the crude extracts and pure compounds indicated chloroform extracts of the leaves exhibited moderate activity and only gleinadiene (2)showed moderate activity against Bacillus cereus. trans Isomer of Gleinadiene (2) has never been reported from this plant previously.